Nutrient requirements of fish (National Academy Press, 1993)
Dietary requirements, energy, protein and amino acids, lipids, carbohydrates, minerals -- Vitamins -- Other dietary components -- Water -- Fiber -- Hormones -- Antibiotics -- Antioxidants -- Pigments -- Pellet binders -- Feeding stimulants -- Antinutrients and adventitious toxins -- Antinutrients present in feedstuffs -- Natural contaminants of feedstuffs -- Heavy metals -- pesticides -- Digestibility and absorption -- Methods of digestibility determination -- Factors affecting digestibility -- Nutrient digestibility -- Diet formulation and processing -- Use of nutrient requirement data -- Formulating fish diets -- Commercial diet ingredients -- Quality of ingredients -- Feed processing -- Natural ingredient reference diets -- Purified research diets -- Feeding practices -- Feeding larval fish -- Channel catfish -- Tilapia -- Striped bass and hybrid bass -- Rainbow trout -- Pacific salmon -- Atlantic salmon -- Nutrient requirements table -- Composition of feed ingredients.